KAJIAN RANTAI PASOK DAN PENDAPATAN USAHA PEMBENIHAN IKAN - Musarlin Musarlin; Ayub M. Padangaran; Muhaimin Hamzah (Jurnal Sosio Agribisnis, 2017)
The system of chain supply in goldfish hatchery enterprise can be detected through the members of the chain, flow of the chain, and process of chain in goldfish hatchery business. The purposes of this study were to analyze the system of supply chain in goldfish hatchery enterprise, to analyze incomes generated from the goldfish hatchery enterprise, to analyze the correlation between the system of supply chain and incomes generated from the goldfish hatchery enterprise. The study was conducted at Unit Pembenihan Rakyat (UPR) in Konawe Regency in province of Sulawesi Tenggara, from April to September 2014. The population in this study was all farmers that own the UPR. Determination of respondents is done by census method. The number of respondents is 8 people. Data analysis was carried out in a qualitative descriptive way to assess supply chain systems, while the Kendal Rank Correlation analysis was used to determine the relationship of supply chain systems with goldfish hatchery income. The results of the study show that the supply chain mechanism of the goldfish hatchery commodity involves main suppliers, hatchery farmers, farmer-collectors, government, and farmer-raisers or end consumers. The flow of the goldfish hatchery commodity consists of three chains, namely: main suppliers à hatchery farmers à government à farmer-raiser; main suppliers à hatchery farmers à farmer-raiser, and main suppliers à hatchery farmers à farmer-collectors. The Kendal coefficient correlation was 90.6%, which indicates a significant correlation between supply chain and incomes generated from goldfish hatchery enterprise. Keywords: supply chain; goldfish hatchery; income; UPR; Konawe Regency